2021
DOI: 10.2106/jbjs.oa.21.00076
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Social Media for Recruitment by Orthopaedic Surgery Residency Programs

Abstract: Background: As the use of social media continues to rise, the presence of social media accounts among orthopaedic surgery residency programs can foster connections with other specialties, highlight departmental achievements, and be a resource for applicants to learn more about the program. This study evaluated the current utility and landscape of social media, with an emphasis on the use of Instagram, in orthopaedic surgery residency programs in the United States. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 17 publications
(21 reference statements)
1
36
0
Order By: Relevance
“…This study includes the most detailed analysis to date of content included in orthopaedic residency program Instagram posts. It reinforces findings of previous studies on orthopaedic programs 11-13 and on dermatology, 14,15 general surgery, 16 plastic surgery, 10,17 and vascular surgery 18 programs that these Instagram posts are most often used to introduce applicants to residents and, to a lesser extent, faculty. A large emphasis seems to be placed on depicting what life is like for residents outside the hospital.…”
Section: Discussionsupporting
confidence: 87%
“…This study includes the most detailed analysis to date of content included in orthopaedic residency program Instagram posts. It reinforces findings of previous studies on orthopaedic programs 11-13 and on dermatology, 14,15 general surgery, 16 plastic surgery, 10,17 and vascular surgery 18 programs that these Instagram posts are most often used to introduce applicants to residents and, to a lesser extent, faculty. A large emphasis seems to be placed on depicting what life is like for residents outside the hospital.…”
Section: Discussionsupporting
confidence: 87%
“…Some studies, such as an analysis on the use of Instagram by orthopaedic residency programs for recruitment, have begun to emerge in this arena. 12 These social media networks have become increasingly important during the COVID-19 pandemic and have the potential to continue conveying important health information in the future. 13,14 However, it is also worth noting that these social media networks still compete with a vast amount of hospital, clinic, and specialty society webpages that feature public health and educational topics.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). These results are echoed in the study by Malyavko et al, who assessed the utility of social media for recruitment by orthopaedic surgery residency programs 6 . They demonstrated that most residency program Instagram accounts showcased the daily work of residents, a resident biography, or resident life outside of the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty percent of all respondents reported either seeing or being unsure whether they had seen an orthopaedic surgery post that could be considered inappropriate or a violation of patient privacy. There are currently no universal guidelines for social media use in the orthopaedic surgery community, and uncertain ethical and legal standards remain 6 . A 2017 study by Call et al reviewed online content posted by 1,021 orthopaedic surgeons across social media platforms, identifying some form of unprofessional content from 3.5% of surgeons 12 , 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation